INCREASING EMPLOYMENT AND SOCIAL CHANGE (Annual of the Faculty of Philosophy in Skopje, 2010)
High unemployment rates that exist in Macedonia for a longer period created problems of active population, but also uncertainty and for future generations who come completing the educational process and who appear on the labor market; on which long period of time remain as inactive.The formation of an acceptable social model is an issue which raises serious considerations: how to restrict market imperfections and on their place institutions, especially state, local governments, to shape social processes and social changes, how to help vulnerable laser of population, especially for his employment, not to endanger the reasons for working engagement.Encouraging employment requires preparation and innovation of strategy for employment, programs to encourage entrepreneurship and small businesses, then reforms in labor legislation, particularly encouraging employment of unemployed and socially excluded persons on various grounds, state, municipal level and the level of individual requirements. This leads to desirable social changes in the society.
Keywords: UNEMPLOYMENT; EMPLOYMENT; GROWTH; SOCIAL CHANGES; ENTREPRENEURSHIP